Answer:
ever find the answer? I cant manage to find it
Y=gradient x + zeroth term
Y=2x+5
I got -6/25 Sorry I can't really explain this try web2.0calc.com it helps alot with math.
Answer: a) add n+1 to the previous term
b) add the previous two terms
d) subtract n+1 from the previous term
e) multiply the previous term by 3
f) subtract 2 from previous term then add 5 to the next term
<u>Step-by-step explanation:</u>
a) 1, 3, 6, 10
∨ ∨ ∨
+2 +3 +4 The next term is 10 +5 = 15
b) 1, 2, 3, 5
∨ ∨ ∨
=3 =5 =8 The next term is 5 + 8 = 13
d) 8, 7, 5, 2
∨ ∨ ∨
-1 -2 -3 zThe next term is 2 - 4 = -2
e) 1, 3, 9, 27
∨ ∨ ∨
×3 ×3 ×3 The next term is 27 × 3 = 81
f) 49, 47, 52, 50, 55
∨ ∨ ∨ ∨
-2 +5 -2 +5 The next term is 55 - 2 = 53
The following term is 53 + 5 = 58
I count five 'k's there, so that part of the expression is
k⁵ .
Two 'n's form the rest of it, so that part is n² .
The parts are multiplied, so the simplest form of the expression is
k⁵ n² .